Penguatan karakter pancasila melalui model pembelajaran kooperatif tipe STAD (Student Achievement Division) siswa kelas IV pada mata pelajaran PPKn di SD Inpres Bontomanai Kec. Tamalate Kota Makassar: Penelitian Kualitatif Deskriptif - Handayani, Putri; Yumriani; Rismawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the strengthening of tolerance and responsibility characters through the STAD (Student Teams Achievement Division) cooperative learning model for grade IV students in PPKn subjects at SD Inpres Bontomanai, Tamalate District, Makassar City and to determine the factors that cause the strengthening of tolerance and responsibility characters in PPKn subjects for grade IV students through the STAD (Student Teams Achievement Division) cooperative learning model at SD Inpres Bontomanai, Tamalate District, Makassar City. This type of research is descriptive qualitative. Data collection techniques in this study are observation, interviews and documentation.